ANALISIS EKONOMI PADA USAHA BUDIDAYA KERAMBA IKAN PATIN (Pangasius sp) DI DANAU GAP DESA LONG IRAM KOTA KECAMATAN LONG IRAM - Fahrie Husaini; Qoriah Saleha; Said Abdusysyahid (2339-1324, 2023)
The purpose of this study was to determine the expenditure and revenue of the catfish business and the feasibility of catfish farming in Lake Gap, Long Iram Village, City based on the RCR, Payback Period, and ROI indicators. This research was conducted from November 2021 to July 2022. Sampling used the census method by using a total of 10 respondents, namely cultivators in Lake Gap. The main data (primary) was obtained from cultivators by means of interviews using a list of questions. The results of the analysis show that the expenditure is Rp. 42,336,000/year/respondent and the income is Rp. 80,220,000/year/respondent. Based on the RCR, Payback Period, and ROI indicators, the RCR is 1.3, the Payback Period is 1.8 and the ROI is 55.83, these results indicate that the business is feasible to run.Keywords: Cages, Catfish, Economic Analysis